PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN TEKNIK KATA MENGALIR BERBANTUAN MEDIA BENDA KONKRET PADA SISWA KELAS VIII SMPN 5 PAGENTAN - Romelah Romelah (Center of Language and Cultural Studies, 2016)
The aim of this study is to improve the ability to write poetry with the technique of flow-assisted media said concrete objects. This study uses a classroom action research. The process of the implementation of this action research refers to the spiral model Kemmis and Tagart with four steps include research, planning, implementation, observation, and reflection consisting of two cycles. Results of the research cycle I the average value of 69.70 students with classical completeness 50%. Results of the second cycle the average value of 78.86 with 95.45% classical completeness. These results are supported by the results of the questionnaire statement of the student's interest first cycle of 81.81% increased in the second cycle to 100%. Based on the above results it can be concluded that the use of media-assisted techniques flowing said concrete objects can improve the quality of the processes and outcomes of learning to write poetry.